1990
DOI: 10.1103/physrevlett.64.677
|View full text |Cite
|
Sign up to set email alerts
|

Selective equilibration among the current-carrying states in the quantum Hall regime

Abstract: The Hall resistance of a two-dimensional electron gas is measured with gated probes to determine the extent of equilibration among the TV current-carrying states in the quantum Hall regime. After traveling macroscopic distances (-80 /im), current injected into the first state is equilibrated among the TV-1 lowest states but equilibration into the highest state varies strongly across the Hall plateau. This is attributed to a change in the TVth state from being localized within a magnetic length of the edge to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
87
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(96 citation statements)
references
References 15 publications
9
87
0
Order By: Relevance
“…93. The Shubnikov-De Haas maximum at 5 2 T, for example, is found to disappear at gate voltages such that the pomt contact conductance is equal to, or smaller than 2e 2 /h, which means that the pomt contact only transmits two spm-spht edge channels The number of occupied spm-spht Landau levels m the bulk at this magnetic field value is 3 This expenment thus demonstrates that the Shubnikov-De Haas oscillations result from the highest-mdex edge channel only, presumably because that edge channel can penetrate mto the bulk via states in the bulk Landau level with the same mdex that coexist at the Fermi level (cf Section 19 c) Moreover, it is found that this edge channel does not scatter to the lower-mdex edge channels over the distance of 250 μιη from probe p to drain d, consistent with the expenment of Alphenaar et al 429 In Section 19 a we discussed how an "ideal" contact at the 2DEG boundary mduces a local equihbnum by equipartitiomng the outgomg current equally among the edge channels The anomalous Shubnikov-De Haas effect provides a direct way to study this contact-mduced equihbration by means of a second pomt contact between the pomt contact voltage probe p and the current dram d in (Fig 5b), m this case with a l 5-μιη Separation between pomt contact p and the second pomt contact It is found that the Shubnikov-De Haas oscillations m R 3l are suppressed only if the second pomt contact has a conductance of (2e 2 /h)(N vllde . -1) or smaller At larger conductances the oscillations m R 3t return, because this pomt contact can now couple to the highest-mdex edge channel and distnbute the backscattered electrons over the lower-mdex edge channels The pomt contact positioned between contacts p and d thus functions äs a controllable "edge channel mixer "…”
Section: A Ideal Contactssupporting
confidence: 73%
See 4 more Smart Citations
“…93. The Shubnikov-De Haas maximum at 5 2 T, for example, is found to disappear at gate voltages such that the pomt contact conductance is equal to, or smaller than 2e 2 /h, which means that the pomt contact only transmits two spm-spht edge channels The number of occupied spm-spht Landau levels m the bulk at this magnetic field value is 3 This expenment thus demonstrates that the Shubnikov-De Haas oscillations result from the highest-mdex edge channel only, presumably because that edge channel can penetrate mto the bulk via states in the bulk Landau level with the same mdex that coexist at the Fermi level (cf Section 19 c) Moreover, it is found that this edge channel does not scatter to the lower-mdex edge channels over the distance of 250 μιη from probe p to drain d, consistent with the expenment of Alphenaar et al 429 In Section 19 a we discussed how an "ideal" contact at the 2DEG boundary mduces a local equihbnum by equipartitiomng the outgomg current equally among the edge channels The anomalous Shubnikov-De Haas effect provides a direct way to study this contact-mduced equihbration by means of a second pomt contact between the pomt contact voltage probe p and the current dram d in (Fig 5b), m this case with a l 5-μιη Separation between pomt contact p and the second pomt contact It is found that the Shubnikov-De Haas oscillations m R 3l are suppressed only if the second pomt contact has a conductance of (2e 2 /h)(N vllde . -1) or smaller At larger conductances the oscillations m R 3t return, because this pomt contact can now couple to the highest-mdex edge channel and distnbute the backscattered electrons over the lower-mdex edge channels The pomt contact positioned between contacts p and d thus functions äs a controllable "edge channel mixer "…”
Section: A Ideal Contactssupporting
confidence: 73%
“…This demonstrates that the n = 2 and n = l edge channels have almost fully equilibrated. A quantitative analysis 429 shows that, in fact, 92% of the current originally injected into the n = l edge channel is 677 (1990) redistributed equally over the n = l and n = 2 channels, whereas only 8% is transferred to the n = 3 edge channel. The suppression of scattering between the highest-index n -N edge channel and the group of edge channels with n =ζ N -l was found to exist only if the Fermi level lies in (or near) the Nth bulk Landau level.…”
Section: A Ideal Contactsmentioning
confidence: 99%
See 3 more Smart Citations